A retórica do desarmamento: uma análise de proferimentos de parlamentares sobre o comércio de armas de fogo e munição no Brasil - Maysa de Padua Teixeira (2007)
The aim of this studied is to assesses the aspects of rhetoric argumentation developed by parliamentarians around disarmament in Brazil, focused on violence, criminality, public security, and personal rights. The corpus chosen in this research is constituted of twodiscourses belonged to politic parliament kind. One of them stated by Alberto Fraga (PFL/DF), federal deputate who was against the prohibition of weapon trade. The other of them was stated by Raul Jungmann (PPS/PE), who was favorable this prohibition. It was analyzed the previous conditions of argumentation, the performance of the deputate asspeaker and his interlocutor, technical reasoning in order to persuade, the values mobilized through their discourses, and, finally, the ethos construction in this statements. The analysis followed the theoretical postulates of Novel Rhetoric, added by studies on linguistics markersof argumentation.